PENGARUH PENERAPAN SISTEM E-FILING, SOSIALISASI PERPAJAKAN, DAN TINGKAT KEPERCAYAAN PADA PEMERINTAH TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA JAKARTA SETIABUDI DUA - Muhammad Atito (2023)
This study aims to determine whether there is influence from the implementation of the e-filing system, tax socialization, and the level of trust in the government on individual taxpayer compliance at KPP Pratama Jakarta Setiabudi Dua. This study uses a quantitative method with the sample being individual taxpayers who are registered and active at KPP Pratama Jakarta Setiabudi Dua. The sampling technique used probability sampling with a total sample of 150 respondents. The data is processed and tested using the SEM-PLS method. The results of this study indicate that the implementation of the e-filing system and the level of trust in the government have a positive effect on individual taxpayer compliance at KPP Pratama Jakarta Setiabudi Dua. Meanwhile, tax socialization has no effect on individual taxpayer compliance at KPP Pratama Jakarta Setiabudi Dua.